2019
DOI: 10.20546/ijcmas.2019.811.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhizobium Inoculation on Yield and Nodule Formation of Cowpea

Abstract: There is a great possibility to increase production of legume plants by exploiting better colonization of their root and rhizosphere through rhizobial inoculation, which can fix atmospheric nitrogen and protect nature from pollution. Of the several legumes, cowpea is also known for their high

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…The well plant growth and better production indicators (pods, seeds and yield) observed in both assays agree with previous studies that demonstrated positive effects associate to the important symbiotic relationship Rhizobium-legume [10,11]. There are direct and indirect effects of Rhizobium inoculation on the nodule formation in cowpea, which help to fix nitrogen in soil as well as increases the fertility of the soil [34]. In the case of this research, numerous nods appeared before 50 days after planting.…”
Section: Discussionsupporting
confidence: 91%
“…The well plant growth and better production indicators (pods, seeds and yield) observed in both assays agree with previous studies that demonstrated positive effects associate to the important symbiotic relationship Rhizobium-legume [10,11]. There are direct and indirect effects of Rhizobium inoculation on the nodule formation in cowpea, which help to fix nitrogen in soil as well as increases the fertility of the soil [34]. In the case of this research, numerous nods appeared before 50 days after planting.…”
Section: Discussionsupporting
confidence: 91%
“…1) Our results showed a positive effect of rhizobial inoculation of on the growth and yield of soybean in field trials. Growth status of pods number, grains number, hundred-grain weight and nodules number with rhizobial inoculation were better than the control group (Figure 9), supporting previous results in which inoculation with rhizobia had a promoting effect on crop growth [6,39,40].…”
Section: Discussionsupporting
confidence: 87%